Single and Binary Biosorption isotherms of Different Heavy Metal Ions Using Fungal Waste Biomass - Al-Hares, Hasanain Saad (Al-Nahrain Journal for Engineering Sciences, 2017)
The ability of fungal waste biomass type White Agaricus Bisporus to biosorb Pb(II) ,Cr(III), Cd(II) and Co(II) from wastewater was investigated in batch process. Single and binary mixtures were used at low metal concentration wastewater treatment. The size of the biosorbent ranged 0.3-1 mm. The biosorption capacity of the biosorbent was evaluated under equilibrium conditions at 25 °C. Results indicated that the biosorption capacity of waste of fungi for the binary mixture was always lower than that for a single component system. Eight isotherm models were used to fit the experimental data of single system and Langmuir model was found a suitable to describe the biosorption data. The maximum uptake capacity (qe) of Pb(II), Cr(III), Cd(II) and Co(II) in single system was 158.73, 46.94, 40.16 and15.94 mg/g respectively with correlation coefficients 0.999,0.998,0.988 and 0.991 respectively. For binary system, four biosorption models were used to fit the experimental data. Extended Langmuir model gave the best fitting. The removal percentage of heavy metals onto fungal waste biomass was in order of Pb(II) > Cr(III) > Cd(II) > Co(II) in both single and binary system. The results show that the using waste of fungi as a biosorbent of heavy metals gave a higher uptake capacity of four heavy metals.